A Cross-Sectional Study: Orthorexia Nervosa In Regular Exercising Individuals For Healthy Life - Yesildemir, Ozge; Acar Tek, Nilufer (Progress in Nutrition, 2022)
This study was conducted to determine the prevalence of orthorexia nervosa (ON) among individuals who exercise regularly and to define the factors associated with ON. A total of 206 individuals, (102 males and 104 females) who exercise regularly at least twice a week were included in the study. Anthropometric measurements were taken and body composition was measured by BIA in addition to energy. Also, nutrient intake was done through a 24-hour diet recall and the ORTO-15 test was applied to the participants. Orhtorexia was more prevalent among participants who exercise regularly (81.6%). There was no statistically significant relationship between orthorexic tendency or gender, marital status, education, and income. The mean exercise frequency was significantly higher in individuals with ON than in non-ON individuals. Total dietary energy intake and the percentage of energy from carbohydrates were higher in males with ON than in non-ON males. The percentage of energy from protein was higher in females with ON. Body weight, percentage of body fat, and BMI were higher in orthorexic females than in non-orthorexic females, while there was no difference in anthropometric measurements and body composition in relation to ON in males. As a result, it was determined that individuals who exercise regularly were a risk group in terms of ON.